Socialization Sorting, Waste Management, Waste Treatment In Selokerto Village, Sempor, Kebumen - Kusumastuti, Kusumastuti; Mutoharoh, Siti; Rahmadhani, Wulan; Dewi, Adinda Putri Sari (Prosiding University Research Colloquium, 2022)
Garbage is material that is disposed of as residue from industrial and householdproduction. Garbage is the residue of human daily activities and/or natural processes insolid form (Law Number 81, 2012). The amount of waste produced in a certain area isproportional to the number of residents, types of activities, and the level of consumptionof the population for goods or materials. The larger the population or the level ofconsumption of goods, the greater the volume of waste produced (Sucipto, 2012).Selokerto Village is one of the villages in Sempor sub-district with an area of 150hectares. Based on preliminary results, it was found that most of the people of Selokertoare still not aware of environmental health with a classification of about 57% of residentsthrowing garbage and waste in rivers, 37% in the yard, 3% in the fields and 3% throwinggarbage in its place. There needs to be concern from the Selokerto village community tominimize the existing waste into the Selokerto village environment.This community service was carried out by conducting socialization about wastemanagement to the residents of Selokerto village which was attended by 30 peopleconsisting of RW, RT, Kadus and cadres. Before and after the socialization, a pre-test andpost-test of the residents' knowledge about waste management were conducted. Theresults of the pre-test found that 60% of the residents did not know how to process waste.And after the socialization, the post test results showed that 80% of the residents hadgood knowledge of waste management. After the socialization, residents were also invitedto do community service simultaneously in the Selokerto village area to maintain a cleanenvironment. In conclusion, there is a need for public awareness and the need for wastemanagement for the importance of maintaining environmental cleanliness in theSelokerto village area.